Gathering for Open Science Hardware 2016. Issue 1 (24th April 2017) - Dosemagen, Shannon; Liboiron, Max; Molloy, Jenny
Without hardware, there is no science. Instruments, reagents, computers, and other equipment are essential for producing systematic knowledge. Yet, current supply chains limit access and impede creativity and customization through high mark-ups and proprietary designs, compounded by proprietary hardware licenses and patents. Open Science Hardware (OSH) addresses part of this problem by sharing designs, instructions for building, and protocols. Expanding the reach of OSH within academic research, NGO initiatives, citizen science, and education has potential to increase access to experimental tools and facilitate their customization and reuse. We organized with others the "Gathering for Open Science Hardware" (GOSH) in 2016 to address what we see as the primary barrier to OSH: early adopters are disparate and separated by geographical and disciplinary borders which limit interaction, exchange and community building. This inaugural gathering brought together 50 of the most active developers, users, and thinkers in the OSH movement, complemented by expertise from diverse backgrounds, to seed a global community. This article provides a review of the activities and debates we conducted at GOSH 2016.